Analisis tentang Studi Komparatif antara Hukum Kewarisan Islam dan Hukum Kewarisan Adat - Akhmad Haries (FENOMENA, 2014)
The conflicts of legacy claim are always found in the society. The causes of this problem are the weakness awareness of the people about how to distribute a fair legacy and the juridical problems related to the hereditary law implemented in Indonesia. Hereditary laws, widely applied in Indonesia, are Islamic hereditary law and traditional custom hereditary law. These two configurations of the law, certainly, will have more advance problematical consequences. The heirs should choose the two juridical options. These two options have similirities and differences fundamentally about the definitions of the legacy, the base of the legacy, the system of the legacy, the rank of the heirs, and the amount of the legacy.